2014
DOI: 10.1016/j.fob.2014.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin‐3‐glucoside increases low‐density lipoprotein receptor (LDLR) expression, attenuates proprotein convertase subtilisin/kexin 9 (PCSK9) secretion, and stimulates LDL uptake by Huh7 human hepatocytes in culture

Abstract: HighlightsQuercetin-3-glucoside can increase LDLR expression by hepatocytes.Quercetin-3-glucoside can reduce PCSK9 secretion by hepatocytes.Quercetin-3-glucoside can down regulate sortilin expression.Quercetin-3-glucoside can increase LDL uptake by hepatocytes.Quercetin-3-glucoside is a potential anti-cholesterolemic agent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(47 citation statements)
references
References 48 publications
2
45
0
Order By: Relevance
“…Although we did not look specifically at NPC1 expression or cholesterol levels in this study, it is possible that Q3G may affect a cholesterol-or NPC-1-related process and thereby prevent Ebola virus entry. The involvement of cholesterol metabolism is compatible with experimental data demonstrating that Q3G upregulates the low-density lipoprotein (LDL) receptor (LDLR) and the uptake of LDL cholesterol in human hepatocytes (30).…”
Section: Discussionsupporting
confidence: 83%
“…Although we did not look specifically at NPC1 expression or cholesterol levels in this study, it is possible that Q3G may affect a cholesterol-or NPC-1-related process and thereby prevent Ebola virus entry. The involvement of cholesterol metabolism is compatible with experimental data demonstrating that Q3G upregulates the low-density lipoprotein (LDL) receptor (LDLR) and the uptake of LDL cholesterol in human hepatocytes (30).…”
Section: Discussionsupporting
confidence: 83%
“…An increase in cellular PCSK9 could be the result of more production, less degradation, or less secretion of the protein. We have previously shown that, in cultured Huh7 hepatocytes, Q3G reduced the production and the secretion of PCSK9, while dramatically increasing the production and the cell‐surface localization of LDLR . Here, we examined how mouse pancreatic beta cells in culture responded to exposure to Q3G.…”
Section: Resultsmentioning
confidence: 99%
“…Previously, we examined how this flavonoid affected PCSK9 and LDLR expression by Huh7 human hepatocytes. We showed that, at single‐digit micromolar levels, Q3G inhibited PCSK9 secretion and stimulated LDLR expression at the cell surface, resulting in a greater uptake of exogenous LDL‐C . The opposite regulation of these molecular determinants of plasma cholesterol may partly explain the anti‐dyslipidemic benefit of Q3G.…”
Section: Introductionmentioning
confidence: 92%
“…Since liver tissue is the primary site for PCSK9 expression 14 , it might be due to physiological characteristics of extra-hepatic tissues that excess SREBP-2 increases LDL uptake due to LDLR over-expression. 15,16 There is a controversy over the function of PCSK9 and SREBP-2, since the former internalizes LDLR while the latter induces it. Furthermore, regression analyses showed that circulating PCSK9 is more closely associated with serum cholesterol-related parameters than SREBP-2 expression levels are.…”
Section: Discussionmentioning
confidence: 99%